Optical reset modulation in the SiO 2 /Cu conductive-bridge resistive memory stack - Kawashima, Tomohito (2017)
We show that the negative photoconductivity property of the nanoscale filamentary breakdown path in the SiO2 electrolyte of the SiO2/Cu conductive bridge resistive random access memory (CBRAM) stack is affected by the number of positive-voltage sweeps applied to the Cu electrode (with respect to a non-metal counter electrode). The path's photo-response to white light, of a given intensity, is suppressed with an increasing number of applied positive-voltage sweeps. When this occurs, the path may only be disrupted by the light of a higher intensity. It is further shown that the loss of the path's photosensitivity to the light of a given intensity can be recovered using a negative-voltage sweep (which eliminates the path), followed by the reformation of the path by a positive-voltage sweep. The above behavior is, however, not seen in the SiO2/Si stack (which involves a non-metal Si electrode), suggesting that the photo-response modulation effect is related to the Cu electrode. The demonstrated reversible electrical modulation of the path's photo-response may afford greater flexibility in the electro-optical control of the CBRAM device.